2017
DOI: 10.1016/j.ajpath.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Col5a2 Expression Result in Novel Skin and Adipose Abnormalities and Predisposition to Aortic Aneurysms and Dissections

Abstract: Classic Ehlers-Danlos syndrome (cEDS) is characterized by fragile, hyperextensible skin and hypermobile joints. cEDS can be caused by heterozygosity for missense mutations in genes COL5A2 and COL5A1, which encode the α2(V) and α1(V) chains, respectively, of collagen V, and is most often caused by COL5A1 null alleles. However, COL5A2 null alleles have yet to be associated with cEDS or other human pathologies. We previously showed that mice homozygous null for the α2(V) gene Col5a2 are early embryonic lethal, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 38 publications
2
24
0
1
Order By: Relevance
“…In addition, miR-125 promoted apoptosis by reducing the expression of VEGF (Wu et al, 2018 ), which is possibly associated with the neovascularization required by the hydatid cyst metabolism in patients with cystic echinococcosis (Matera et al, 2018 ). Egr-miR-10a-5p was predicted to target the NECTIN2, COLGALT1, COL5A2 , and DDTL genes, which were involved in the positive regulation of natural killer cell–mediated cytotoxicity and T-cell receptor signaling pathway, collagen fibril organization, collagen catabolic process, tumor necrosis factor production, and ERK1 and ERK2 cascades, respectively (Stanietsky et al, 2013 ; Park et al, 2017 ; Miyatake et al, 2018 ). It has been reported that hsa-miR-10a-5p had a role in regulating the proliferation and invasiveness of cancer cells and inflammatory responses in endothelial cells (Vaher et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-125 promoted apoptosis by reducing the expression of VEGF (Wu et al, 2018 ), which is possibly associated with the neovascularization required by the hydatid cyst metabolism in patients with cystic echinococcosis (Matera et al, 2018 ). Egr-miR-10a-5p was predicted to target the NECTIN2, COLGALT1, COL5A2 , and DDTL genes, which were involved in the positive regulation of natural killer cell–mediated cytotoxicity and T-cell receptor signaling pathway, collagen fibril organization, collagen catabolic process, tumor necrosis factor production, and ERK1 and ERK2 cascades, respectively (Stanietsky et al, 2013 ; Park et al, 2017 ; Miyatake et al, 2018 ). It has been reported that hsa-miR-10a-5p had a role in regulating the proliferation and invasiveness of cancer cells and inflammatory responses in endothelial cells (Vaher et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al, indicated that the decrease of COL5A2 expression could induce femoral head necrosis (Yang et al, 2018). Park et al, demonstrated that abnormal expression of COL5A2 may lead to new abnormalities in skin and adipose tissue, which can further lead to the occurrence of aortic aneurysms and dissections (Park et al, 2017). Park et al, demonstrated that homozygosity and heterozygosity for null COL5A2 alleles produced embryonic lethality and a novel classic Ehlers-Danlos syndrome-related phenotype (Park et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To reveal the selection signatures of the Wannan Black pig during domestication and breeding, we first selected regions within the top 1% of F ST and π ratios and found five protein coding genes: peptidylprolyl isomerase domain and WD repeat containing 1, which is one of the three classes of peptidylprolyl isomerases found in all eukaryotic and prokaryotic organisms, and viruses, assisting in protein folding [35]; ADAM metallopeptidase with thrombospondin type 1 motif 6, which has been found to be associated with cardiac conduction [36]; tripartite motif containing 23, whose function remains largely unknown; collagen type V alpha 2 chain, which has been shown to be associated with aortic aneurysms and dissections [37]; and centromere protein K, which has been shown to be associated with catastrophic chromosome segregation defects [38]. GO and KEGG analysis of six genes showed significant association with the digestive system and metabolism, which to some extent may indicate their involvement in the crude-feed tolerance of the Wannan Black pig breed.…”
Section: Discussionmentioning
confidence: 99%